Experimental research on the water precipitation performance of polymer colloid and fly ash colloid and their applications as fire extinguishing materials in mines - Shang, Yuyang (Frontiers in Earth Science, 2023)
In this paper, polymer colloid and fly ash colloid fire extinguishing materials are selected. Through experimental preparation and water precipitation characteristics research, colloid fire extinguishing materials and optimal concentration ratio suitable for Binchang mining area are selected to effectively control the fire area. The results show that, the higher the concentration of polymer colloidal powder mixed with water, the shorter the gelling time. After the fly ash is mixed with the gelling agent and water, when the concentration ratio of fly ash to water remains the same, the greater the concentration of the gelling agent, the shorter the gelling time. After the colloid is left standing for 24 h, the smaller the concentration is, the more water is precipitated, and the higher the water precipitation rate is. Through comparison, it was found that when the polymer colloid was selected as the fire extinguishing material, with the concentration ratio of polymer colloid material to water being 3.5%–4%: 96.5%–96%, effective control could be achieved over the fire zones in the goaf of Binchang mine. The research is of great reference value for the control of mine fires.